Zingiber officinale (Roscoe) mitigates CCl4-induced liver histopathology and biochemical derangements through antioxidant, membrane-stabilizing and tissue-regenerating potentials - Gracious Oluwamayowa Oke; Adegboyega Adeleke Abiodun; Christian Eseigbe Imafidon; Barinem Fortune Monsi (Toxicology Reports, 2019)
The world-wide increasing incidence of liver injury has attracted scientific interest in the exploration of better treatment or adjuvant treatment therapies. This study investigated the effects of methanol extract of Zingiber officinale (Roscoe) rhizome (MEZOR) in a Wistar rat model of carbon tetrachloride (CCl4)-induced liver injury. The study recruited thirty female Wistar rats that received graded doses of MEZOR (determined by its LD50) by oral gavage through an oral canula, for 4 consecutive weeks following 1 week oral administration of CCl4 (0.7 ml/kg in olive oil; 1:1, v/v) while livolin forte® (5.2 mg/kg p.o.) was used as a standard. CCl4 induced deleterious hepatic effects as revealed by the liver function biomarkers (AST, ALT, ALP and total protein), antioxidant indicators (GSH and CAT) and histopathological effects, demonstrated by H & E, Gordon and Sweet, Masson’s trichrome, PAS staining techniques as well as by quantificational analyses of the liver micrographs, using image–J. MEZOR treatment was associated with a dose-dependent and significant mitigation of the aforementioned parameters (p < 0.05). This study concluded that MEZOR is a potential therapeutic choice in the adjuvant treatment of subjects with chemically-induced liver injury. Keywords: CCl4, Zingiber officinale, Liver injury, Histopathology, Female Wistar rats